(untitled) (Research Announcements "Heritage BG", 2025)
The article presents the work on two important projects, based on which new knowledge is created related to the disclosure of the content and features of the described primary sources – Slavonic menaia and other manuscripts and rare and valuable books from the Church-Historical and Archival Institute (CHAI) of the Bulgarian Patriarchate, from the Regional Museum of History (RMH) – Lovech and from the Regional Library ‘Prof. Benyu Tsonev’(RL) – Lovech on the one hand, as well as with the proposal for the creation of a multifunctional model on the other hand. The model aims to use the same data on the content and specific features of documents for different purposes and offers specific approaches in building information resources to make them more useful for future research, more widely available, more adaptive in subsequent technological transformations. References: Hristova-Shomova 2018: Hristova-Shomova, Iskra. Dragotin miney: balgarski rakopis ot nachaloto na XII v. zapazen kato palimpsest v Dragotiniya apostol (NBKM 880). Sofiya. Knizhovnoto 2011: Knizhovnoto nasledstvo v balgarskite biblioteki: Rezultati ot prouchvane. Sofiya. [onlinе]. Available from: http://www.lib.bg/kragli_masi/Knizhovno_nasledstvo_doklad.pdf Natsionalna 2013: Natsionalna strategiya i programa za opazvane na knizhovnoto kulturno nasledstvo v bibliotekite i osiguryavane na dostap do nego: Proekt. Sofiya. [onlinе]. Available from: https://www.lib.bg/publish Yovcheva 2014: Yovcheva, Mariya. Starobalgarskiyat sluzheben miney. Sofiya.